KAJIAN ALTERNATIF MODEL KELEMBAGAAN KOPERASI PEGAWAI REPUBLIK INDONESIA (KP-RI) DI KOTA PEKANBARU - ,; ,; ,; , (Kurs : Jurnal Akuntansi, Kewirausahaan dan Bisnis, 2023)
This research is to clarify two aspects of Kelembagaan Koperasi Pegawai Republik Indonesia (The organization of Indonesian civil servent cooperative), which are what the profile  currently inplemented and what should the organisazation be designed in the future. The objek of the research is cooperative of Indonesian civil servent as shorted in KP-RI in Pekanbaru City. The research categories as qualitative research, where data were collected from the cooperative practist and academicients. The research have identified two altenratif model of the KP-RI organization, namedly “One for Each Model”, where in each government office and school is fasilited with one cooperative, and “One for some Model”, whare some government offices and schools are facilited with one cooperative. This research recommended “One for Some Model”, sepecialy for the cooperative wihin the Instansi Vertical, which under centra government control. The conseguencies of “One for Some Model” would be a merger (amalgamasi) some of current cooperatives to become one cooperative. Penelitian ini untuk mengklarifikasi dua aspek Kelembagaan Koperasi Pegawai Republik Indonesia (Koperasi Pegawai Negeri Sipil Indonesia), yaitu bagaimana profil yang dijalankan saat ini dan organisasi yang akan dirancang seperti apa selanjutnya. Objek penelitian ini adalah Koperasi Pegawai Negeri Sipil Indonesia yang disingkat KP-RI di Kota Pekanbaru. Kategori penelitian ini adalah penelitian kualitatif, dimana data dikumpulkan dari praktisi koperasi dan akademisi. Penelitian ini mengidentifikasi dua model alternatif organisasi KP-RI, yaitu “ One for Each Model ”, dimana di setiap kantor pemerintah dan sekolah difasilitasi dengan satu koperasi, dan “ One for some Model ”, dimana beberapa kantor pemerintah dan sekolah berada difasilitasi oleh satu koperasi. Penelitian ini merekomendasikan “One for Some Model”, khususnya untuk koperasi di lingkungan instansi vertikal yang berada di bawah kendali pemerintah pusat. Konsekuensi dari “ One for Some Model ” adalah penggabungan (amalgamasi) beberapa koperasi yang ada menjadi satu koperasi.